ANALISIS PENILAIAN KINERJA KEUANGAN BANK UMUM SYARIAH (BUS) DENGAN PENDEKATAN ISLAMICITY PERFORMANCE INDEX PERIODE 2021-2023 - Sri Anggraini; Hesi Eka Puteri (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to determine the financial performance of Islamic Commercial Banks with the islamicity performance index approach. The background of the author choosing this title is because the conventional approach that only focuses on financial ratios such as Return on Assets (ROA) and Return on Equity (ROE) is not sufficient to describe the overall performance of Islamic banks. A more comprehensive approach is needed, such as the Islamicity Performance Index, to assess other aspects of performance that are more in line with sharia principles. This research is a quantitative descriptive method. This study uses four indicators of islamicity performance index, namely profit sharing ratio, zakat performance ratio, islamic income vs non islamic income, and islamic investment vs non islamic investment. The population in this study was 13 Islamic commercial banks. Sampling using purposive sampling method at Islamic commercial banks registered with the Financial Services Authority (OJK) during the 2021-2023 period. Based on the results of data analysis and discussion, the research results show that the financial performance of Islamic Commercial Banks for the 2021- 2023 period using the islamicity performance index approach shows the overall result of obtaining a score of 4 with a satisfactory predicate. Profit sharing ratio shows a score of 4 with a satisfactory predicate. For the zakat performance ratio, all banks still have a score of 1 with an unsatisfactory predicate. Islamic income vs non Islamic income, and Islamic investment vs non Islamic investment obtained a very satisfactory predicate, except Bank Mega Syariah obtained a score of 3 with a fairly satisfactory predicate on Islamic income vs non Islamic income. With this research, it can contribute to Islamic Commercial Banks to evaluate their performance which is still in the unsatisfactory category and maintain good performance.